Error diagnóstico de Apendicectomía en el adulto. Instituto Ecuatoriano de Seguridad Social. Riobamba, 2018. - Astorga Fuenmayor, Ysamar Carolina (2019)
Acute appendicitis is a disease of spontaneous appearance and surgical resolution. The quality of the diagnosis of appendicitis depends on the way in which the diagnostic tools are applied, the most useful being the Alvarado scale. The rapid or inaccurate evaluation of patients in the emergency services can lead to unnecessary surgery that is not free of morbidity and mortality, which can result in a diagnostic error. In addition, since the diagnosis is mostly clinical, the signs and symptoms of patients can vary, producing doubts, for which it is supported by imaging tests or a blood laboratory. Objectives: To demonstrate that the diagnostic error of appendicitis causes the extirpation of a normal appendix. Material and methods: Non-experimental, descriptive, retrospective research in adult patients aged 25 to 75 years who met the inclusion criteria. A population of 338 appendectomized patients was studied, of which 73 were white appendectomies. The data were obtained from the statistical base of the general surgery service. Conclusions: It was proved that the diagnostic error of appendicitis caused the extirpation of a helthy organ in 21.65% of the total cases registered in 2018, of which 76.71% met the diagnostic criteria of Alvarado assuming that the error occurs due to poor handling of this scale. There was a prevalence of males between 25 and 35 years of age.